Collagenase injections for the treatment of single cords in cases of Dupuytren’s contracture – a prospective intervention study of long-term experience with Xiapex - Fischer, Lisa Maria; Dahmann, Sonja; Simunec, Denis; Meyer-Marcotty, Max V. (GMS German Plastic, Reconstructive and Aesthetic Surgery – Burn and Hand Surgery, 2017)
Introduction: The gold standard in the treatment of Dupuytren’s contracture is surgical therapy. Alternatives are percutaneous needle fasciotomy and radiation in exceptional cases. Injection treatments with Xiapex (Pfizer) are a new therapy option. This collagenase, extracted from clostridium histolyticum, is used to break down the affected tissue cords. The objective of this study is to examine the effect and long-term success of treatment with Xiapex.Methods: In this study, Xiapex treatment was conducted on a sample group of 19 patients with Dupuytren’s contracture. The injection was placed either on the cord at the level of the metacarpophalangeal (MCP) joint (n=17) or of the proximal interphalangeal (PIP) joint (n=7). Break-up of the cord occurred 24 hours after the injection. The neutral zero method was used to assess the extent of movement. The Michigan Hand Outcomes Questionnaire (MHQ) was selected for evaluation of the general hand function in 16 patients. The WHO-5 and the EQ-5D VAS Score were used as a measure of the patients’ satisfaction and their state of health. All values were collected both pre-injection as well as 1 year post-injection.Results: Out of 19 patients in our sample group, 16 patients (≈84%) benefitted in terms of improvement in mobility. Overall, the range of movement increased by Ø 26° in the affected finger. A separate assessment demonstrated that:The range of movement increased by 77% in the MCP joint. The extent of movement pre-injection was Ø (0-28-78) and post-injection it was Ø (0-9-81) with an improvement of Ø 22°. In the PIP joint, only slight improvement was observed (Ø pre (0-27-93); post (0-24-95)).The MHQ increased from Ø 76% (R: 32–97%) to 81% (R: 39–100%).The painfulness decreased from Ø 19% (R: 0–55%) to Ø11% (R: 0–55%), corresponding to Ø 43%. Satisfaction increased in 72% of patients by Ø 21%.According to WHO-5, patient satisfaction pre-injection was Ø 20 (R: 11–25), and 1 year after the injection it was Ø 21 (R: 15–25). The general state of health (EQ-5D VAS) did not change (pre: Ø 78%; post: Ø 78%).Conclusion: Although 84% of patients achieved an improvement in function, the effectiveness of Xiapex must continue to be monitored in further studies over an even longer period of time. In addition, the indication for use of Xiapex in cords over the PIP joint should be discussed. In our study, the result of Xiapex treatment in cords over the PIP joint was only marginal, and therefore we continue to apply Xiapex only on cords over the MCP joint. The cost of the medication should also be included in the analysis. Based on information regarding previous results and treatment alternatives, therapy with Xiapex is an option for treatment of Dupuytren’s contracture, especially in the case of individual cords that run over the MCP joint. A future, randomised study should compare the results of collagenase injections and percutaneous needle fasciotomy.